Optimization of process technology and quality analysis of a new yogurt fortified with Morchella esculenta - TONG,Qianqian (2022)
Abstract To optimize the process technology of yogurt fortified with M. esculenta, first, the Plackett-Burman experimental design combined with the central composite design (CCD) were used to investigate the effects of four parameters on the sensory score. Then, artificial neural networks (ANN) and genetic algorithm (GA) were used to evaluate the process parameters of the fortified yogurt. Finally, the quality of the yogurt prepared under optimal conditions were observed. The results showed that the optimal parameters from ANN-GA were: 0.2 g of mycelia, 15 g milk powder, 6.4 g sucrose, and a fermentation temperature of 38 °C, with the highest predicted sensory score of 97.1 points, which was more accurate and reliable than CCD. Mycelia of M. esculenta gave the yogurt excellent quality, including good acidity (95 ± 2.85° T) and water holding capacity (64.32 ± 4.25%) after 21 days storage at 4 °C; firmness (12.98 ± 1.25) g, consistency (22.85 ± 0.92) g·sec, stickness (-6.16 ± 0.38) g, stringiness (3.53 ± 0.12) mm, and cohesion index (-6.62 ± 1.75) g·sec. Moreover, the living lactic acid bacteria of the yogurt with M. esculenta (6.23 ± 0.23) × 107 CFU/mL) were significantly higher than that of the control yogurt (5.65 ± 0.31) × 107 CFU/mL. This could provide a theoretical basis and parameter guidance for developing a new functional yogurt.